The Existence of Artisanal Small-Scale Gold Mining in Indonesia, The Impact of Public Health and Environmental Sustainability : A Narrative Review - Elanda Fikri; Yura Witsqa Firmansyah; Anshah Silmi Afifah; Mhd. Fauzi (JURNAL KESEHATAN LINGKUNGAN, 2023)
Introduction: This study reviewed the negative impacts of artisanal small-scale gold mining (ASGM). This paper presents an examination of ASGM's impact on health, with the scope of discussion covering human diseases and disorders, toxic substances, public and miners' safety, environmental damage, socioeconomic conditions. This study contributes mitigation recommendations for ASGM in Indonesia. This research subject is important because there has not been an ASGM study that has reviewed these aspects in Indonesia. Discussion: Chronic diseases, acute diseases, infectious diseases, and disabilities can threaten local communities' health and survival. Toxic heavy metals such as mercury, cadmium, arsenic, and lead are difficult to avoid in ASGM, since they have a high level of use. Other pollutants generated by ASGM are noise and silicia dust. ASGM has caused accidents with a total of 36 minor injuries, an estimated 57 serious injuries, and 11 deaths. ASGM also causes water, soil, and air pollution; it is a threat to the geology of world heritage sites. ASGM has been proven to improve the community's economy in several parts of Indonesia. Conclusion: ASGM has proven to have a significant impact on public health, environmental sustainability, and the socioeconomic state of Indonesian society. In general, the lack of ASGM legitimization in Indonesia is an enabling factor for these impacts.